2010
DOI: 10.1016/j.jaapos.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

HOXA1 mutations are not a common cause of Möbius syndrome

Abstract: The HOXA1-related syndromes result from autosomal recessive truncating mutations in the homeobox transcription factor, HOXA1. Limited horizontal gaze and sensorineural deafness are the most common features; affected individuals can also have facial weakness, mental retardation, autism, motor disabilities, central hypoventilation, carotid artery and/or conotruncal heart defects. Möbius syndrome is also phenotypically heterogeneous, with minimal diagnostic criteria of nonprogressive facial weakness and impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In our study, it was possible to establish a positive correlation about the presence of the polymorphism G218A in the Hoxa1 when comparing MBS patients and their relatives. Conversely, another study reported that neither participant with Möbius syndrome and autism spectrum disorder harbored the G218A polymorphism [21].…”
Section: Discussionmentioning
confidence: 95%
“…In our study, it was possible to establish a positive correlation about the presence of the polymorphism G218A in the Hoxa1 when comparing MBS patients and their relatives. Conversely, another study reported that neither participant with Möbius syndrome and autism spectrum disorder harbored the G218A polymorphism [21].…”
Section: Discussionmentioning
confidence: 95%
“…The same findings were reported by Strömland et al and Fons‐Estupiña in Europe, and by Gómez‐Valencia et al in Latin America . However, despite the fact that MS is associated with a sporadic condition without family history, in some isolated cases a genetic association related more to alterations to specific genes or families of genes, including translocation and deletion has been described. This association is not possible to generalize, and requires more specific study than a karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…Most individuals with BSAS and ABDS also have bilateral sensorineural hearing loss caused by an absent cochlea and rudimentary inner-ear development and absent or hypoplastic carotid arteries with a corresponding absence of the carotid canal through which the artery normally passes. Approximately 20% of patients with BSAS or ABDS have congenital facial palsy [ 5 ]. Some affected individuals also have intellectual disability, autism spectrum disorder, moderate-to-severe central hypoventilation, swallowing difficulties, vocal cord paresis, conotruncal heart defects, macrocephaly, and malformations of inner ear bones and/or petrous bones.…”
Section: Differential Diagnosis Of Congenital Facial Weaknessmentioning
confidence: 99%